Advantages and Disadvantages of Integrating Video Making in a Speaking Class - Sari, Selvina Novita; Pratolo, Bambang (LPPM Universitas Pancasakti Tegal, 2024)
This study aims to examine the advantages and disadvantages of integrating video production as a teaching tool in a speaking class. Using a qualitative descriptive design, the research was conducted during the 2023–2024 academic year with 15 fifth-semester undergraduate students from the Faculty of Literature, Culture, and Communication at Ahmad Dahlan University, Yogyakarta. Participants were selected through purposive sampling. Data were collected through in-depth structured interviews, allowing students to freely express their experiences and perceptions. The data were analyzed using the five-stage qualitative analysis framework including data collection, coding, pattern identification, interpretation, and reporting. Triangulation was applied to ensure credibility through transcript examination, theoretical comparison, and supporting notes. The findings reveal that video production offers several pedagogical benefits. Students reported increased confidence, particularly when speaking in front of a camera, improvement in speaking skills such as pronunciation and fluency, and the development of technological competence through the use of digital tools. However, the study also identified notable drawbacks, including the time and financial demands of video production, technical and accessibility issues, privacy concerns, and a tendency for some students to prioritize memorization over deep comprehension. Overall, while video production can effectively enhance communication skills and language learning, its implementation requires careful planning, institutional support, and thoughtful instructional design to maximize benefits and minimize limitations.